The Principle of Judges in Determining the Validity of Grounds for Criminal Expungement in the Criminal Justice System in Indonesia: Prinsip Hakim dalam Menentukan Sah Tidaknya Alasan Penghapus Pidana Pada Sistem Peradilan Pidana di Indonesia - Nasrullah, Mochammad Ridho; Hutabarat, Rugun Romaida (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Grounds for the exclusion of criminal liability serve as essential mechanisms within Indonesian criminal law to ensure that punishment is not imposed automatically when the elements of a crime are fulfilled, but instead aligned with substantive justice. Specific Background: Although Articles 48–51 of the Criminal Code regulate justifying and excusing grounds, judicial practice demonstrates variations in how judges assess their validity. Knowledge Gap: Limited scholarship has comprehensively explained the principles applied by judges in determining whether these grounds are legally acceptable, particularly in cases involving psychological conditions and proportionality assessments. Aims: This study aims to analyze the normative framework of grounds for criminal exemption and identify the principles guiding judicial evaluation. Results: The findings show that judges consistently apply the principles of proportionality, subsidiarity, and culpa in causa, while also assessing trial facts, the defendant’s mental state, and the balance between the threat faced and the defensive act. Novelty: This research highlights that judges also consider jurisprudence and customary law as extended bases for exemption beyond the Criminal Code. Implications: These findings underscore the need for consistent judicial guidelines to ensure that the application of grounds for criminal exemption remains aligned with the objectives of criminal law and the pursuit of substantive justice. Highlights: Judges apply proportionality, subsidiarity, and culpa in causa to assess criminal exemption. Trial facts and the defendant’s psychological condition strongly influence judicial decisions. Jurisprudence and customary law expand exemption grounds beyond the written Criminal Code. Keywords: Criminal Exemption, Judicial Principles, Proportionality, Indonesian Criminal Code, Substantive Justice